Europe and America : criss-crossing perspectives, 1788-1848 - Portes, Jacques (Paris : Centre d'Études Nord-Américaines, E.H.E.S.S, 1987)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: internationale relaties; Amerika; Europa